THE EPIDEMIOLOGICAL SURVEY OF HUMAN INTESTINAL PARASITES IN RURAL AREAS OF LARIJAN - M. Rezaian; M. Seraei (Tehran University of Medical Sciences, 1992)
This Survey was carried out from June to October 1990, in order to evaluate the prevalence of intestinal parasites in the residents. A total of 2227 persons were selected from 44 Villages by using linear Systematic Sampling Method. The Samples of stool from these people were examined by formalin - ether concentration procedure. The collected data were analyzed by spss package. The result showed that 69.2% of the specimens were infected with intestinal parasites, which 58.4% of them were pathogenic (33.8% 16.9%, and 7.7% were infected with 1,2 and 3 species intestinal pathogen parasites respectively). Infection rates with intestinal pathogen parasites was higher in mountains (71.4%) than plain areas (49.6%). and also higher in age groups 5-14 years (68.0%) than other age groups. The difference of the infection rates was nonsignificant between males and females. Prevalence of different intestinal parasites was as follows: Protozoa; E.Coli 27.9% G. lamblia 17.2% I.butschlii 7/0% E.histolytica 5.9% E. hartmann 2.9% E. nana 2. 1% D. fragilis). 6% and C.. mesnili 0.4% Helminths; T. trichiura 26. 8% A. lumbricoides 17.8% Hook worm 8.9% S. stercoralis 8.5% E. vermicularis 3. 6% T.saginata 1. 4%, H.nana %1.0 and Trichostrongylus sp. 0.7%